Contemporary performance measurement systems: A review of their consequences and a framework for research - Franco-Santos, Monica; Lucianetti, Lorenzo; Bourne, Mike (Elsevier, 2012)
The main purpose of this paper is to develop a conceptual framework for understanding the literature on the consequences of contemporary performance measurement (CPM) systems and the theories that explain these consequences. The framework is based on an in-depth review of 76 empirical studies published in high-quality academic journals in the areas of accounting, operations, and strategy. The framework classifies the consequences of CPM into three categories: people's behaviour, organizational capabilities, and performance consequences. This paper discusses our current knowledge on the impact of CPM, highlighting inconsistencies and gaps as well as providing direction for future research.